Impact of midazolam vs. saline on effect size estimates in controlled trials of ketamine as a rapid-acting antidepressant - Wilkinson, Samuel T; Farmer, Cristan; Ballard, Elizabeth D; Mathew, Sanjay J; Grunebaum, Michael F; Murrough, James W; Sos, Peter; Wang, Gang; Gueorguieva, Ralitza; Zarate, Carlos A (Neuropsychopharmacology, 2019)
The goal of this study was to infer the effectiveness of midazolam as a comparator in preserving the blind in ketamine studies for mood disorders through patient-level analyses of efficacy trial outcomes. In this integrative data analysis (k = 9, N = 367 patients with mood disorders), clinical outcomes were compared across four groups: ketamine (midazolam-controlled), ketamine (saline-controlled), midazolam, and saline. Ketamine doses ranged from 0.5 to 0.54 mg/kg and midazolam doses ranged from 0.02 to 0.045 mg/kg. The baseline-to-Day 1 effect size was d = 0.7 (95% CI: 0.4-0.9) for ketamine (midazolam) versus midazolam and d = 1.8 (95% CI: 1.4-2.2) for ketamine (saline) versus saline. The effect of ketamine relative to control was larger in saline-controlled studies than in midazolam-controlled studies (t(276) = 2.32, p = 0.02). This was driven by a comparatively larger effect under midazolam than saline (t(111) = 5.40, p < 0.0001), whereas there was no difference between ketamine (midazolam) versus ketamine (saline) (t(177) = 0.65, p = 0.51). Model-estimated rates of response (with 95% CI) yielded similar results: ketamine (midazolam), 45% (34-56%); ketamine (saline), 46% (34-58%); midazolam, 18% (6-30%); saline, 1% (0-11%). The response rate for ketamine was higher than the control condition for both saline (t(353) = 7.41, p < 0.0001) and midazolam (t(353) = 4.59, p < 0.0001). Studies that used midazolam as a comparator yielded smaller effects of ketamine than those which used saline, which was accounted for by greater improvement following midazolam compared to saline.
Keywords: Ketamine; Saline Solution; Humans; lidé středního věku; Midazolam; Depressive Disorder, Major; antidepresiva; ketamin; Antidepressive Agents; dospělí; Female; výsledek terapie; lidé; solný roztok; bipolární porucha; Adult; depresivní porucha unipolární; midazolam; ženské pohlaví; Male; Middle Aged; Bipolar Disorder; Treatment Outcome; klinické zkoušky jako téma; Clinical Trials as Topic; mužské pohlaví